Undergraduate students’ errors in integral calculus: A cognitive load theory perspective - Suharti Suharti; Puji Qur’ani Al Haq (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2026)
This study aims to analyze students' errors in solving integral calculus problems based on Newmann's Error Analysis (NEA) and relate them to the Cognitive Load Theory (CLT) perspective. This study employs a descriptive quantitative approach, involving 74 students selected by purposive sampling because they have learned integral material in calculus courses. Data were obtained through an integral calculus test and analyzed using descriptive statistics, including grouping errors according to NEA, tabulating frequencies and percentages, calculating proportions and standard deviations of proportions, and presenting data in tables. The results showed that the most dominant student errors were transformation errors with a high category, which are related to difficulties in choosing the right integral technique, followed by process skill errors due to inappropriate algebraic procedures or symbol manipulation, and comprehension errors, which indicate a relatively good understanding of the problem concept, both in the moderate category. Reading errors and encoding errors were not found, indicating that students were able to read and write answers correctly. From a CLT perspective, the high intrinsic cognitive load in integral calculus material causes transformation and process skill errors, while process skill errors also reflect extraneous cognitive load due to inefficient information management. Moderate comprehension errors indicate that germane cognitive load is managed quite well, although students still have difficulty selecting the appropriate technique and performing algebraic manipulations. These results confirm that students' primary difficulties in integral calculus lie in selecting integration techniques and processing information during the solution process.